THE IMPORTANCE OF THE INNOVATIVE APPROACH IN THE ACTIVITIES OF THE TRANSNATIONAL CORPORATION - Mahmudov, Ravshanbek Mashrabboy o‘g‘li (Educational Research in Universal Sciences, 2024)
The article examines the necessity of developing existing Transnational Corporations (TNCs) into three innovations. It examines the reasons why TNCs should focus on innovation, the role of innovative TNCs in the global economy, and the relationship between research and development (R&D) resources and total TNC revenues. By examining this, the article presents an assessment of the importance of innovation for the growth and success of TNCs. This article is primarily based on statistics published this year by visualcapitalist.com, statista.com, companiesmarketcap.com, and is the result of an analysis based on an econometric model.